Yasmin the builder - Faruqi, Saadia; Aly, Hatem (North Mankato, Minnesota : Picture Window Books, 2019)
As their makerspace project the students in Yasmin's second grade class are building a city: there are houses, a school, a church, even a castle, but Yasmin is not sure what to build--until inspiration strikes.
1.7
K-3
520L
K
Keywords: Muslim girls -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Makerspaces -- Juvenile fiction; Creative ability -- Juvenile fiction; Elementary schools -- Juvenile fiction; Muslims -- Fiction; Pakistani Americans -- Fiction; Makerspaces -- Fiction; Creative ability -- Fiction; Building -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Readers (Elementary) -- Fiction